A double network gel adsorbent based on fluorinated modified cellulose and its preparation method and application
Through the dual network gel adsorbent based on fluorination-modified cellulose, the problems of high cost and insufficient selectivity of lithium ion targeted adsorbents are solved, efficient directional adsorption and recycling of lithium ions are achieved, and lithium battery waste treatment is provided. Effective method.
Patent Information
- Application Number
- CN202410529426.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-28
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-04-28
AI Technical Summary
The existing lithium-ion targeted adsorbents have problems such as expensive, prone to secondary pollution and poor selectivity in lithium resource recycling, which limits their large-scale application.
Using a dual network gel adsorbent based on fluorination modified cellulose, the high-quality preparation was prepared by pre-oxidizing Chinese medicine waste residue and organic fluorine source solution. Lithium ion adsorbent with selectivity and mechanical strength.
It realizes efficient directional selection adsorption of lithium ions, is low-cost and stable in materials, and is suitable for lithium ions extraction and recycling in complex water bodies, providing a solution for lithium battery waste liquid treatment.
Smart Images

Figure CN118437295B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion adsorbents, and in particular to a double network gel adsorbent based on fluorinated modified cellulose, and a preparation method and application thereof. Background Art
[0002] Due to the booming development of new energy technologies, the global demand for lithium is expected to reach 1.5 million tons by 2050. The supply and demand of lithium resources are already out of balance, which makes the mining and recycling of lithium resources on a global scale of great significance. At present, the targeted recovery of Li(I) faces multiple difficulties and challenges. Many water treatment technologies have been tried for the recovery of Li(I). However, due to problems such as recovery purity, reactor construction, and cost control, its practical application has certain limitations.
[0003] The adsorption method has broad application prospects due to its advantages such as low cost, high degree of equipment, strong targeted functionality, recyclability and no waste mud and waste residue generation. The extraction and recovery of Li(I) are seriously affected by the interference of a large number of coexisting substances and the occupation of adsorption sites by naturally similar metal ions with high ion concentrations. Some new Li(I) targeted adsorbents (such as crown ether-based polymers, lithium ion cage adsorbents, sub-nanoscale ion channel crystal materials, etc.) have been reported, but they have limitations such as high price, easy to produce secondary pollution and unsatisfactory selectivity among coexisting ions, which restrict their large-scale application. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a double network gel adsorbent based on fluorinated modified cellulose and its preparation method and application. The preparation method provided by the present invention has mild conditions and low cost, and the obtained adsorbent has good directional selective adsorption for lithium ions.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a double network gel adsorbent based on fluorinated modified cellulose, comprising the following steps:
[0007] The Chinese medicine waste residue is heated and mixed with a potassium persulfate aqueous solution, and subjected to a pre-oxidation treatment to obtain a pre-oxidized Chinese medicine residue;
[0008] The pre-oxidized Chinese medicine residue is mixed with an organic fluorine source solution and subjected to ultrasonic treatment to obtain a fluorinated cellulose nanofiber precursor solution;
[0009] The fluorinated cellulose nanofiber precursor solution is mixed with N-N'methylenebisacrylamide, acrylamide, an initiator and an organic solvent to carry out a polymerization reaction to obtain a double network gel adsorbent based on fluorinated modified cellulose.
[0010] Preferably, the concentration of the potassium persulfate aqueous solution is 0.2-0.4 mol / L, and the volume ratio of the mass of the traditional Chinese medicine waste residue to the potassium persulfate aqueous solution is 0.5-1.5 g:100 mL.
[0011] Preferably, the pre-oxidation treatment is carried out at a temperature of 60 to 80° C. and for a time of 8 to 10 hours.
[0012] Preferably, the organic fluorine source is dodecafluoroheptyl methacrylate;
[0013] The concentration of the organic fluorine source solution is 0.2-0.3 mol / L.
[0014] Preferably, the power of the ultrasound is 900-1200 W, and the time is 15-25 min.
[0015] Preferably, the mass ratio of the traditional Chinese medicine waste residue to N-N'methylenebisacrylamide and acrylamide is 0.01-0.03:0.021:1;
[0016] The initiator is ammonium persulfate; the mass ratio of the initiator to acrylamide is 1:25-50.
[0017] Preferably, the polymerization reaction temperature is 60-80° C. and the time is 4-6 hours.
[0018] The invention provides a double network gel adsorbent based on fluorinated modified cellulose prepared by the above preparation method.
[0019] The present invention provides application of the double network gel adsorbent based on fluorinated modified cellulose as a lithium ion adsorbent.
[0020] Preferably, the lithium ion adsorbent is used in the field of water treatment.
[0021] The present invention provides a preparation method of a double network gel adsorbent based on fluorinated modified cellulose, comprising the following steps: heating and mixing Chinese medicine waste residue with potassium persulfate aqueous solution, performing pre-oxidation treatment, and obtaining pre-oxidized Chinese medicine residue; mixing the pre-oxidized Chinese medicine residue with an organic fluorine source solution, performing ultrasonic treatment, and obtaining a fluorinated cellulose nanofiber precursor solution; mixing the fluorinated cellulose nanofiber precursor solution with N-N'methylenebisacrylamide, acrylamide, an initiator, and an organic solvent, and performing a polymerization reaction to obtain a double network gel adsorbent based on fluorinated modified cellulose. The double network hydrogel has a nanocrystalline cellulose network, has excellent mechanical strength, and has low synthesis cost, a simple synthesis process, and is harmless to the environment. It is a functional material with good engineering potential. In addition to excellent mechanical strength, the double network hydrogel can also achieve highly selective adsorption of target ions through modification of specific functional groups. Fluorine (F) is a halogen element with the highest electronegativity and the smallest atomic radius, and has strong oxidizing properties. Lithium (Li), as an active alkali metal, has strong reducing ability. According to Lewis acid-base theory, hard alkaline fluoride ions and hard acidic lithium ions have intrinsic strong affinity. The present invention uses a double network gel constructed by fluorinated cellulose and polyacrylamide as a carrier, and introduces F sites with specific coordination with Li(I) through fluorinated cellulose, so that the material can achieve directional selective adsorption of Li(I) in lithium-containing solutions, and constructs a practical porous water treatment adsorption material with high performance, strong targeting, stable structure, high mechanical strength, easy separation and engineering application prospects. The present invention can provide new ideas and solutions for the efficient extraction of Li(I) in complex water bodies, and provide a theoretical basis and strong technical support for the application of adsorption technology in the targeted recovery and resource utilization of Li(I).
[0022] In addition, the present invention is based on the specific coordination effect of fluorine-lithium, and adopts the polymerization and cross-linking method of acrylamide monomers, so the preparation method has mild conditions and low cost. The fluorinated cellulose gel prepared by this method has good mechanical strength, stability and targeted selective adsorption of Li(I). The results of the examples show that the adsorption capacity of the double network gel adsorbent based on fluorinated modified cellulose provided by the present invention for lithium ions in a strong acid environment is greater than 40 mg g -1 , meeting the actual use needs of lithium battery waste liquid; the compressive stress can reach 1.49MPa at the maximum load, the gel is flexible and tough, and can withstand high-intensity compression deformation without any obvious damage. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The adsorption isotherms and kinetics curves of F-1, F-2 and F-3 on Li(I) aqueous solution;
[0024] Figure 2is the adsorption effect of F-2 on 500 mg / L Li(I) solution at different initial pH;
[0025] Figure 3 is the selective adsorption effect of F-2 on Li(I) in a mixed ion solution system;
[0026] Figure 4 The SEM spectra of F-1, F-2, and F-3;
[0027] Figure 5 is the EDS spectrum of F-2;
[0028] Figure 6 FTIR spectra of fluorine-free cellulose gel and F-1, F-2 and F-3;
[0029] Figure 7 The stress-strain test results of acrylamide gel and F-2;
[0030] Figure 8 The adsorption capacity test results of Comparative Examples 3 and 4 are shown. DETAILED DESCRIPTION
[0031] The present invention provides a method for preparing a double network gel adsorbent based on fluorinated modified cellulose, comprising the following steps:
[0032] The Chinese medicine waste residue is heated and mixed with a potassium persulfate aqueous solution, and subjected to a pre-oxidation treatment to obtain a pre-oxidized Chinese medicine residue;
[0033] The pre-oxidized Chinese medicine residue is mixed with an organic fluorine source solution and subjected to ultrasonic treatment to obtain a fluorinated cellulose nanofiber precursor solution;
[0034] The fluorinated cellulose nanofiber precursor solution is mixed with N-N'methylenebisacrylamide, acrylamide, an initiator and an organic solvent to carry out a polymerization reaction to obtain a double network gel adsorbent based on fluorinated modified cellulose.
[0035] The present invention heats and mixes Chinese medicine waste residue with potassium persulfate aqueous solution, and performs pre-oxidation treatment to obtain pre-oxidized Chinese medicine residue. In the present invention, the Chinese medicine in the Chinese medicine waste residue is a Chinese medicine containing cellulose components, and is preferably one or more of Astragalus, Crataegus, and Red Peony Root.
[0036] The present invention preferably pre-treats the waste residue of traditional Chinese medicine, and the pre-treatment preferably comprises the following steps:
[0037] The traditional Chinese medicine waste residue is dried, crushed and sieved to obtain dried traditional Chinese medicine waste residue.
[0038] In the present invention, the drying is preferably carried out in a blast drying oven, the drying temperature is preferably 50-100° C., the drying time is preferably 6-48 h, more preferably 12-36 h.
[0039] The present invention preferably uses a crusher for crushing; in the present invention, the screening is preferably through a 60-mesh sieve.
[0040] In the present invention, the concentration of the potassium persulfate (PMS) aqueous solution is preferably 0.2-0.4 mol / L, more preferably 0.3 mol / L, and the volume ratio of the mass of the Chinese medicine waste residue to the potassium persulfate aqueous solution is preferably 0.5-1.5 g:100 mL, more preferably 1 g:100 mL. In the present invention, the potassium persulfate plays the role of oxidation and bleaching.
[0041] In the present invention, the heating and mixing is preferably carried out in a water bath; the temperature of the pre-oxidation treatment is preferably 80°C, and the time is preferably 10 hours. In the present invention, the Chinese medicine waste residue contains lignin and hemicellulose in addition to cellulose. The present invention uses pre-oxidation treatment to remove lignin and hemicellulose therein and selectively screen out cellulose.
[0042] In the present invention, after the pre-oxidation treatment, the present invention preferably centrifuges the obtained pre-oxidation treatment liquid to obtain pre-oxidized Chinese medicine residues. In the present invention, the centrifugation rate is preferably 6000 rpm.
[0043] After the pre-oxidation treatment, the present invention mixes the pre-oxidized Chinese medicine residue with an organic fluorine source solution and performs ultrasonic treatment to obtain a fluorinated cellulose nanofiber precursor solution. In the present invention, the organic fluorine source is preferably dodecafluoroheptyl methacrylate (DFHMA); the concentration of the organic fluorine source solution is preferably 0.2 to 0.3 mol / L, more preferably 0.25 mol / L; the solvent of the organic fluorine source solution is preferably N,N-dimethylformamide (DMF) and / or dimethyl sulfoxide (DMSO).
[0044] In the present invention, the volume ratio of the mass of the pre-oxidized traditional Chinese medicine residue to the organic fluorine source solution is preferably 0.5-1.5 g:100 mL, more preferably 1 g:100 mL.
[0045] In the present invention, the power of the ultrasound is preferably 900-1200 W, more preferably 1080 W, and the time is preferably 15-25 min, more preferably 20 min. The present invention obtains a uniformly dispersed fluorinated cellulose nanofiber precursor solution by using a short-time high-power ultrasound treatment.
[0046] After obtaining the fluorinated cellulose nanofiber precursor solution, the present invention mixes the fluorinated cellulose nanofiber precursor solution with N-N'methylenebisacrylamide, acrylamide, an initiator, and an organic solvent to carry out a polymerization reaction to obtain a double network gel adsorbent based on fluorinated modified cellulose.
[0047] In the present invention, the initiator is preferably ammonium persulfate (APS). In the present invention, the mass ratio of the initiator to acrylamide is preferably 1:25-50, more preferably 1:30-40.
[0048] In the present invention, the organic solvent is preferably N,N-dimethylformamide (DMF) and / or dimethyl sulfoxide (DMSO).
[0049] In the present invention, the mixing method is preferably: first premixing N-N'methylenebisacrylamide, acrylamide, initiator and organic solvent to obtain a premixed solution; then mixing the fluorinated cellulose nanofiber precursor solution with the premixed solution.
[0050] In the present invention, in the premixed solution, the concentration of N-N'methylenebisacrylamide is preferably 3.2-5.3 g / L, more preferably 4.2 g / L; the concentration of acrylamide is preferably 150-250 g / L, more preferably 200 g / L; the concentration of the initiator is preferably 8-10 g / L, more preferably 8 g / L.
[0051] In the present invention, the mass ratio of the traditional Chinese medicine waste residue to N-N'methylenebisacrylamide and acrylamide is preferably 0.01-0.03:0.021:1, and more preferably 0.02:0.021:1.
[0052] In the present invention, the polymerization reaction temperature is preferably 60 to 80° C., more preferably 60 to 70° C., and the polymerization reaction time is preferably 4 to 6 hours, more preferably 4 to 5 hours.
[0053] In the present invention, after the polymerization reaction, the present invention preferably performs post-treatment on the obtained polymerization product, and the post-treatment preferably comprises the following steps:
[0054] The polymerization product is washed with water, the organic solvent is replaced and dried.
[0055] In the present invention, the water washing and replacement of the organic solvent are preferably carried out under ultrasonic conditions. In the present invention, the drying is preferably carried out in an oven, the drying temperature is preferably 60° C., and the drying time is preferably 24 hours.
[0056] The invention provides a double network gel adsorbent based on fluorinated modified cellulose prepared by the above preparation method.
[0057] The present invention provides the use of the above-mentioned double network gel adsorbent based on fluorinated modified cellulose as a lithium ion adsorbent. In the present invention, the lithium ion adsorbent is preferably used in the field of water treatment, and more preferably used in the treatment of lithium battery waste liquid and lithium battery waste water.
[0058] The double network gel adsorbent based on fluorinated modified cellulose provided by the present invention is described in detail below in conjunction with the examples, but they should not be construed as limiting the scope of protection of the present invention.
[0059] Example 1
[0060] (1) Preparation of fluorinated cellulose nanofiber (F-CNFs) precursor solution
[0061] ① Dry the Chinese medicine waste residue containing water in a blast drying oven at 80°C for 24 hours. Then, use a crusher to break up the Chinese medicine waste residue with a larger size after sufficient drying, and pass it through a 60-mesh screen for later use.
[0062] ② Add 1g of Chinese medicine waste residue into a beaker containing 100mL of PMS aqueous solution (0.3M), place the beaker in a water bath with a preset temperature of 80°C, and stir thoroughly for 10h. Then centrifuge at 6000rpm to obtain white wet residue powder.
[0063] ③ The above white wet drug residue powder was added into a beaker containing 100 mL of fluorinated DMF solution (DFHMA content was 0.25 M), and a short-time high-power ultrasonic treatment was used to obtain a uniformly dispersed fluorinated cellulose nanofiber precursor solution, which was recorded as F-CNFs.
[0064] (2) Preparation of fluorinated cellulose gel F-1
[0065] ① Take 1mL of fluorinated cellulose nanofiber precursor solution (F-CNFs) (containing 0.01g of white drug residue powder) and add it to 4mL of DMF solution containing N-N'methylenebisacrylamide, acrylamide, and ammonium persulfate. The concentration of N-N'methylenebisacrylamide (MBA) in the final mixed solution is 4.2g / L, the concentration of acrylamide (AM) is 200g / L, and the concentration of ammonium persulfate (APS) is 8g / L.
[0066] ②The mixed solution was shaken and placed in an oven at 60°C for 4 hours for polymerization reaction to obtain a transparent fluorinated cellulose gel.
[0067] ③ Then, rinse with a large amount of ultrapure water, place it in an ultrasonic machine to ultrasonically replace the organic solvent DMF, place the gel in an oven to dry for 24 hours, and then cool to room temperature to obtain fluorinated cellulose gel F-1.
[0068] Example 2
[0069] (1) Prepare fluorinated cellulose nanofiber precursor (F-CNFs) according to the method of Example 1.
[0070] (2) Preparation of fluorinated cellulose gel F-2
[0071] ① Take 2mL of fluorinated cellulose nanofiber precursor solution (F-CNFs) (containing 0.02g of white drug residue powder) and add it to 3mL of DMF solution containing N-N'methylenebisacrylamide, acrylamide, and ammonium persulfate. The concentration of N-N'methylenebisacrylamide (MBA) in the final mixed solution is 4.2g / L, the concentration of acrylamide (AM) is 200g / L, and the concentration of ammonium persulfate (APS) is 8g / L.
[0072] ②The mixed solution was shaken and placed in an oven at 60°C for 4 hours for polymerization reaction to obtain a transparent fluorinated cellulose gel.
[0073] ③ Then, rinse with a large amount of ultrapure water, place it in an ultrasonic machine to ultrasonically replace the organic solvent DMF, place the gel in an oven to dry for 24 hours, and then cool to room temperature to obtain fluorinated cellulose gel F-2.
[0074] Example 3
[0075] (1) Prepare fluorinated cellulose nanofiber precursor (F-CNFs) according to the method of Example 1.
[0076] (2) Preparation of fluorinated cellulose gel F-3
[0077] ① Take 3mL of fluorinated cellulose nanofiber precursor solution (F-CNFs) (containing 0.03g of white drug residue powder) and add it to 2mL of DMF solution containing N-N'methylenebisacrylamide, acrylamide, and ammonium persulfate. The concentration of N-N'methylenebisacrylamide (MBA) in the final mixed solution is 4.2g / L, the concentration of acrylamide (AM) is 200g / L, and the concentration of ammonium persulfate (APS) is 8g / L.
[0078] ②The mixed solution was shaken and placed in an oven at 60°C for 4 hours for polymerization reaction to obtain a transparent fluorinated cellulose gel.
[0079] ③ Then, rinse with a large amount of ultrapure water, place it in an ultrasonic machine to ultrasonically replace the organic solvent DMF, place the gel in an oven to dry for 24 hours, and then cool to room temperature to obtain fluorinated cellulose gel F-3.
[0080] Test Example 1
[0081] ① Adsorption isotherm determination
[0082] The adsorption isotherms of fluorinated cellulose gels F-1, F-2, and F-3 were measured respectively as follows:
[0083] Weigh 10 mg of fluorinated cellulose gel and add it to a sample bottle containing 20 mL of Li(I) solution of a certain concentration (50, 100, 200, 300, 400 and 500 mg / L). Then place the sample bottle in a constant temperature shaker at 180 rpm and 25°C for 24 hours. After the sample bottle is allowed to stand, the supernatant is drawn with a syringe and filtered with a 0.45 μm polyethersulfone filter membrane to obtain an aqueous solution of adsorbed Li(I) ions. The Li(I) concentration is determined after dilution. Two parallel tests are performed to ensure the accuracy of the adsorption capacity determination.
[0084] ② Adsorption kinetics determination
[0085] The adsorption kinetics of fluorinated cellulose gels F-1, F-2, and F-3 were measured as follows:
[0086] 50 mg of fluorinated cellulose gel material was added to a beaker containing 100 mL of an initial concentration of 500 mg / L Li(I) aqueous solution. The sample bottle was then placed in a constant temperature shaker and shaken at 180 rpm and 25 °C. 1 mL of the suspension was then taken out using a syringe at different time intervals (0, 10, 30, 60, 120, 300, 480, 720, 1440 min). The suspension was filtered with a 0.45 μm polyethersulfone filter membrane to obtain an aqueous solution of adsorbed Li(I) ions, which was diluted and its Li(I) concentration was determined. Two parallel tests were performed to ensure accurate adsorption capacity determination.
[0087] Figure 1 The adsorption isotherms and kinetics curves of three fluorinated cellulose gels (F-1, F-2, F-3) for Li(I) aqueous solution. Figure 1 a is the adsorption isotherm of the material to Li(I) aqueous solution. The Langmuir model is used to fit the three isotherms. The fitting coefficient R 2 All of them are greater than 0.97, which proves that the Langmuir model is feasible for estimating the adsorption capacity of materials. According to the Langmuir fitting, the theoretical adsorption capacities of three fluorinated cellulose gels F-1, F-2 and F-3 for Li(I) are 43.9, 66.0 and 39.9 mg / g, respectively, among which F-2 has the largest adsorption capacity for Li(I). Figure 1b is the adsorption kinetic curve of the material for Li(I) aqueous solution. The adsorption capacity of the three materials for lithium ions increases rapidly within the first 120 minutes and reaches kinetic equilibrium within 300 minutes. From the adsorption curve, it can be seen that among the three gel materials with different fluorinated cellulose contents, F-2 has the largest adsorption capacity. In summary, F-2 was selected for Li(I) adsorption effect testing in subsequent experiments.
[0088] Test Example 2F-2 Adsorption isotherms at different initial pH
[0089] Weigh 10 mg of F-2 and add it to a sample bottle containing 20 mL of Li(I) solution with a concentration of 500 mg / L and an initial pH of 0, 2, 4, 6, 8, 10, and 12, and then place the sample bottle in a constant temperature shaker at 180 rpm and 25°C for 24 hours. After the sample bottle is allowed to stand, the supernatant is aspirated with a syringe and filtered with a 0.45 μm polyethersulfone filter membrane to obtain an aqueous solution of adsorbed Li(I) ions, which is diluted and its Li(I) concentration is determined. Two parallel tests are performed to ensure the accuracy of the adsorption capacity determination.
[0090] Figure 2 The adsorption effect of F-2 on Li(I) solution with a concentration of 500 mg / L and initial pH of 0, 2, 4, 6, 8, 10, and 12. The results show that the material has the best adsorption capacity under the initial weakly acidic condition (4-6), which can reach 54.5 mg g -1 , the adsorption capacity is still high in the strong acid range, all greater than 40 mg g -1 The adsorption capacity is reduced under alkaline conditions, but the main application scenario in actual use is lithium battery waste liquid, and the background solution pH is acidic, so it also has application potential in actual wastewater.
[0091] Test Example 3F-2 Selective adsorption isotherm determination
[0092] Weigh LiNO3, KNO3, NaNO3, Mn(NO3)2, Mg(NO3)2, and Co(NO3)2 to prepare mixed ion solution systems with concentrations of 100 mg / L and 500 mg / L, take 20 mL of the above two mixed solutions and add them to two sample bottles, then add 10 mg of F-2 adsorbent to each sample bottle. Place the sample bottle in a constant temperature shaker and shake it at 180 rpm and 25 ° C for 24 hours. After the sample bottle is allowed to stand, use a syringe to absorb the supernatant, filter it with a 0.45 μm polyethersulfone filter membrane, and obtain the adsorbed Li(I) ion aqueous solution. Determine its Li(I) concentration after dilution. Perform two parallel tests to ensure the accuracy of the adsorption capacity determination.
[0093] Figure 3The selective adsorption effect of F-2 on Li(I) in a mixed ion solution system with a concentration of 100ppm and 500ppm. The results show that when F-2 is placed in an aqueous solution containing the above-mentioned multiple ions, it still exhibits a high adsorption capacity, while the co-adsorption of other metal ions presents different trend characteristics with different concentrations and valence states. Among them, monovalent Na(Ⅰ) and K(Ⅰ) have competitive adsorption on the material under a concentration of 100ppm, but this co-adsorption disappears when the concentration increases to 500ppm; the opposite is true for divalent Mn(Ⅱ), Co(Ⅱ), and Mg(Ⅱ), and the competitive adsorption under high concentration conditions is higher than that under low concentration conditions, but in general, the fluorinated cellulose gel material of the present invention has a high selectivity for the adsorption of lithium ions.
[0094] Test Example 4: Morphology and element distribution analysis
[0095] SEM-EDS analysis was performed on fluorinated cellulose gels F-1, F-2, and F-3. The obtained SEM images are shown in Figure 4 The results show that with the increase of F content, the surface of the material gradually changes from flat to grooved, and there are small pores distributed on the surface. The small pore structure is conducive to the adsorption of lithium ions on the fluorinated cellulose gel material.
[0096] The element distributions of fluorinated cellulose gels F-1, F-2, and F-3 are shown in Table 1. The EDS spectrum of F-2 is shown in Figure 5 shown.
[0097] Table 1 Element distribution of fluorinated cellulose gels F-1, F-2, and F-3
[0098]
[0099] The signal distribution of C, F, N, and O elements in the EDS spectrum is very uniform, which also indicates the uniform synthesis of the material. Among them, the content of F increases from F-1 to F-2 as the content of fluorinated cellulose increases, while F-3, although the content of fluorinated cellulose added is the highest, the proportion of F in the material decreases, indicating that the F element is not fully and effectively combined in the synthesis process of the F-3 material. The corresponding reduction in the lithium ion adsorption capacity also indirectly indicates that the material's adsorption of lithium ions mainly depends on the specific binding of F.
[0100] Comparative Example 1
[0101] (1) Preparation of cellulose nanofiber precursor solution
[0102] ① Dry the Chinese medicine waste residue containing water in a blast drying oven at 50-100°C for a certain period of time (6-48 hours). Then, use a crusher to break the Chinese medicine waste residue with a larger size after sufficient drying, and pass it through a 60-mesh screen for later use.
[0103] ② Add 1g of Chinese medicine waste residue into a beaker containing 100mL of PMS aqueous solution (0.3M), place the beaker in a water bath with a preset temperature of 80°C, and stir thoroughly for 10h. Then centrifuge at 6000rpm to obtain white wet residue powder.
[0104] ③ The white wet drug residue powder was added into a beaker containing 100 mL of DMF solution (DFHMA content was 0.25 M), and a short-time high-power ultrasonic treatment was used to obtain a uniformly dispersed cellulose nanofiber precursor solution, which was recorded as CNFs.
[0105] (2) Preparation of cellulose gel
[0106] ① Take 2 mL of the cellulose nanofiber precursor solution (CNFs) obtained in Example 1 and add it to 3 mL of DMF mixed solution containing 4.2 g / L N-N'methylenebisacrylamide (MBA), 200 g / L acrylamide (AM) and 8 g / L ammonium persulfate (APS).
[0107] ②The mixed solution was shaken evenly and placed in an oven at 60°C for 4 hours for polymerization reaction to obtain a transparent cellulose gel.
[0108] ③ Then, rinse with a large amount of ultrapure water, place it in an ultrasonic machine to ultrasonically replace the organic solvent DMF, place the gel in an oven to dry for 24 hours, and then cool to room temperature to obtain a fluorine-free cellulose gel, which is recorded as F-free.
[0109] Comparative Example 2
[0110] (1) 1000 mg of acrylamide was added to a 5 mL DMF mixture containing 4.2 g / L N-N'-methylenebisacrylamide (MBA) and 8 g / L ammonium persulfate (APS).
[0111] (2) The mixed solution was shaken and placed in an oven at 60°C for 4 h for polymerization to obtain a transparent acrylamide gel.
[0112] (3) Subsequently, the gel was rinsed with a large amount of ultrapure water and placed in an ultrasonic machine to ultrasonically replace the organic solvent DMF. The gel was placed in an oven to dry for 24 h and then cooled to room temperature to obtain acrylamide gel.
[0113] Test Example 5
[0114] The functional groups of the fluorine-free cellulose gel in Comparative Example 1 and the four materials F-1, F-2 and F-3 were characterized by FTIR. The results are as follows: Figure 6 shown.
[0115] It can be seen that the curve has a peak at 3300-3500cm -1and 2850-3000cm -1 The stretching vibration peaks at 1650-1750cm -1 The stretching vibration peak at 1000-1400 cm -1 The peak signal that appears in the range corresponds to the existence of CF bonds. Compared with the gel without fluorinated cellulose, F-1 and F-2 have obvious CF peak signals, and with the increase of F content, the CF peak signal is strengthened, corresponding to the increase of adsorption capacity. Although the F content of F-3 increases, the CF peak is significantly weakened, indicating that the more F content is not necessarily better, and excessive F content may cause changes in material synthesis, which also corresponds to the fact that the adsorption capacity of F-3 is the lowest in the thermodynamic adsorption experiment.
[0116] Test Example 6
[0117] The acrylamide gel in Comparative Example 2 and F-2 were subjected to stress-strain tests, and the results were as follows: Figure 7 As shown. The results show that the use of fluorinated cellulose as a precursor to form a double network gel can significantly improve the mechanical strength of the gel. Acrylic gel without fluorinated cellulose cannot withstand 70% compressive strain, and the compressive stress at the maximum load is only 0.128MPa, while the compressive stress of fluorinated cellulose gel can reach 1.49MPa at the maximum load. The gel is flexible and tough and can withstand high-intensity compression deformation without any obvious damage.
[0118] Comparative Example 3
[0119] (1) Preparation of cellulose nanofiber precursor solution
[0120] ① Dry the Chinese medicine waste residue containing water in a blast drying oven at 50-100°C for a certain period of time (6-48 hours). Then, use a crusher to break the Chinese medicine waste residue with a larger size after sufficient drying, and pass it through a 60-mesh screen for later use.
[0121] ② Add 1g of Chinese medicine waste residue into a beaker containing 100mL of PMS aqueous solution (0.3M), place the beaker in a water bath with a preset temperature of 80°C, and stir thoroughly for 10h. Then centrifuge at 6000rpm to obtain white wet residue powder.
[0122] ③ The white wet drug residue powder was added into a beaker containing 100 mL of fluorinated DMF solution (hexafluorobutyl methacrylate content was 0.25 M), and a short-time high-power ultrasonic treatment was used to obtain a uniformly dispersed cellulose nanofiber precursor solution, which was recorded as CNFs-F6.
[0123] (2) Preparation of cellulose gel
[0124] ① Take 2 mL of the cellulose nanofiber precursor solution (CNFs-F6) obtained in step (1) and add it to 3 mL of DMF mixed solution containing 4.2 g / L N-N'methylenebisacrylamide (MBA), 200 g / L acrylamide (AM) and 8 g / L ammonium persulfate (APS).
[0125] ②The mixed solution was shaken evenly and placed in an oven at 60°C for 4 hours for polymerization reaction to obtain a transparent cellulose gel.
[0126] ③ Then, rinse with a large amount of ultrapure water, place it in an ultrasonic machine to ultrasonically replace the organic solvent DMF, place the gel in an oven to dry for 24 hours, and then cool to room temperature to obtain a cellulose gel containing F6-2.
[0127] Comparative Example 4
[0128] (1) Preparation of cellulose nanofiber precursor solution
[0129] ① Dry the Chinese medicine waste residue containing water in a blast drying oven at 50-100°C for a certain period of time (6-48 hours). Then, use a crusher to break the Chinese medicine waste residue with a larger size after sufficient drying, and pass it through a 60-mesh screen for later use.
[0130] ② Add 1g of Chinese medicine waste residue into a beaker containing 100mL of PMS aqueous solution (0.3M), place the beaker in a water bath with a preset temperature of 80°C, and stir thoroughly for 10h. Then centrifuge at 6000rpm to obtain white wet residue powder.
[0131] ③ The white wet drug residue powder was added into a beaker containing 100 mL of fluorinated DMF solution (nonafluorohexyl methacrylate content of 0.25 M), and a short period of high-power ultrasonic treatment was performed to obtain a uniformly dispersed cellulose nanofiber precursor solution, which was recorded as CNFs-F9.
[0132] (2) Preparation of cellulose gel
[0133] ① Take 2 mL of the cellulose nanofiber precursor solution (CNFs-F9) obtained in step (1) and add it to 3 mL of DMF mixed solution containing 4.2 g / L N-N'methylenebisacrylamide (MBA), 200 g / L acrylamide (AM) and 8 g / L ammonium persulfate (APS).
[0134] ②The mixed solution was shaken evenly and placed in an oven at 60°C for 4 hours for polymerization reaction to obtain a transparent cellulose gel.
[0135] ③ Then, rinse with a large amount of ultrapure water, place in an ultrasonic machine to ultrasonically replace the organic solvent DMF, place the gel in an oven to dry for 24 hours, and then cool to room temperature to obtain a fluorine-free cellulose gel, recorded as F9-2.
[0136] The adsorption capacity experimental results of Comparative Examples 3 and 4 are as follows: Figure 8 As shown. Figure 8 It can be seen that compared with F-2, the adsorption capacity of F6-2 and F9-2 fluorinated materials for lithium ions is significantly reduced. On the one hand, the optimization of fluorine monomers shows that dodecafluoroheptyl methacrylate has the best polymerization effect in this system, and more F monomers are successfully introduced, providing sufficient fluorination sites for the adsorption of lithium ions. On the other hand, compared with F-2, the gel materials synthesized by hexafluorobutyl methacrylate and nonafluorohexyl methacrylate are denser and have smaller pore sizes, which have certain steric hindrance for the adsorption of lithium ions, making it impossible to effectively utilize the fluorination sites inside the gel material.
[0137] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a double network gel adsorbent based on fluorinated modified cellulose, comprising the following steps: The Chinese medicine waste residue is heated and mixed with a potassium persulfate aqueous solution, and subjected to a pre-oxidation treatment to obtain a pre-oxidized Chinese medicine residue; The pre-oxidized Chinese medicine residue is mixed with an organic fluorine source solution, and subjected to ultrasonic treatment to obtain a fluorinated cellulose nanofiber precursor solution; the organic fluorine source is dodecafluoroheptyl methacrylate; and the concentration of the organic fluorine source solution is 0.2-0.3 mol / L; The fluorinated cellulose nanofiber precursor solution is mixed with N-N'methylenebisacrylamide, acrylamide, an initiator, and an organic solvent to carry out a polymerization reaction to obtain a double network gel adsorbent based on fluorinated modified cellulose; the mass ratio of the traditional Chinese medicine waste residue to N-N'methylenebisacrylamide and acrylamide is 0.01-0.03:0.021:
1.
2. The preparation method according to claim 1, characterized in that: The concentration of the potassium persulfate aqueous solution is 0.2-0.4 mol / L, and the volume ratio of the mass of the traditional Chinese medicine waste residue to the potassium persulfate aqueous solution is 0.5-1.5 g:100 mL.
3. The preparation method according to claim 1 or 2, characterized in that: The temperature of the pre-oxidation treatment is 60-80° C. and the time is 8-10 hours.
4. The preparation method according to claim 1, characterized in that: The power of the ultrasound is 900-1200W, and the time is 15-25min.
5. The preparation method according to claim 1, characterized in that: The initiator is ammonium persulfate; the mass ratio of the initiator to acrylamide is 1:25-50.
6. The preparation method according to claim 1 or 5, characterized in that: The polymerization reaction temperature is 60-80° C. and the reaction time is 4-6 hours.
7. A double network gel adsorbent based on fluorinated modified cellulose prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the double network gel adsorbent based on fluorinated modified cellulose as claimed in claim 7 as a lithium ion adsorbent.
9. The use according to claim 8, characterized in that: The lithium ion adsorbent is used in the field of water treatment.
Citation Information
Patent Citations
Preparation method and application of porous hydrogel adsorbent based on astragalus mongholicus waste residue
CN112934205A
Preparation method for modifying fluorine-containing functional group adsorbent by taking cellulose as carrier
CN116173915A